(untitled) (REME-Revista Mineira de Enfermagem, 2001)
This article presents the results of an ergonomic study carried out in the Human Milk Bank of a Hospital. It describes the activities performed by the staff of the Unit, whose main objectives are to facilitate the babies breast-feeding in the Kangaroo Ward and to assist mothers in Obstetric Ward that face breast-feeding difficulties. The ergonomic research showed the strong affective content of the tasks that can be explained by the emotional and cultural difficulties involved in breast-feeding. This result led to discussion about the social or natural nature of breastfeeding.